1979
DOI: 10.1007/bf01968131
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the role of endogenous copper in the acute inflammatory process

Abstract: The development of two models of acute inflammation (carrageenan-induced foot oedema and pleurisy) was studied in rats after 1 month of a 0.2 p.p.m. copper-deficient diet and after 5 months of a 0.6-0.8 p.p.m. copper-deficient diet. A 'pro-inflammatory' effect of copper deficiency was observed with the 0.2 p.p.m. diet, whilst no effect was evident following the 0.6-0.8 p.p.m. copper deficient diet. These results are briefly commented upon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This hypothesis received further support from our studies on copper-deficient rats. We showed that a severe copper-deficiency produces a statistically significant increase of the foot swelling and of the pleural exudate volume following carrageenan injections [21,25]. Our results were recently confirmed by DENKO [26].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This hypothesis received further support from our studies on copper-deficient rats. We showed that a severe copper-deficiency produces a statistically significant increase of the foot swelling and of the pleural exudate volume following carrageenan injections [21,25]. Our results were recently confirmed by DENKO [26].…”
Section: Introductionsupporting
confidence: 91%
“…As pointed out earlier in this paper the induction of a copperdeficiency status produces an exacerbation of the inflammatory response in the rat. It is now relevant to stress that these copper-deprived rats are likely to be less protected from free radical damage than are normal animals, since copperdeficiency may also induce a significant decrease of both ceruloplasmin [21,25,39] …”
Section: Hours After the Irritantmentioning
confidence: 99%
“…We have shown that copper-deficient rats are more prone to the effects of standard acute inflammatory agents compared with animals on a normal copper diet (Milanino, Mazzoli, Passarella, Tarter & Velo, 1978;Milanino, Conforti, Fracasso, Franco, Leone, Passarella, Tarter & Velo, 1979). Moreover a sharp rise of copper concentration and caeruloplasmin activity in biological fluids and tissues has been measured in man and animals under a wide variety of acute and chronic inflammatory conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in two models of acute inflammation (carrageenan-induced foot pad oedema and pleurisy), a copper deficiency was found to exert a pro-inflammatory effect [13]. However, using the 'phenanthroline assay', attempts to detect copper ions in a form which promotes the generation of "OH or 'crypto-'OH' radical species in fresh serum or SF collected from patients with RA have been unsuccessful [14].…”
Section: Introductionmentioning
confidence: 99%